3D Nanoporous Gold with Very Low Parting Limit Derived from Au‐Based Metallic Glass and Enhanced Methanol Electro‐oxidation Catalytic Performance Induced by Metal Migration. Issue 1 (22nd September 2017) - Xu, Yi; Yiu, Pak Man; Shan, Guangcun; Shibayama, Tamaki; Watanabe, Seiichi; Ohnuma, Masato; Huang, Wei; Shek, Chan‐Hung
Abstract: Nanoporous gold (NPG) with bi‐continuous ligaments and pores structure has promising potential in functional applications, among which one prominent example is fuel cell electrocatalysts. However, current application of NPG is mostly limited to methanol electro‐oxidation (MOR) due to its weak catalytic performance. Here we report a simple chemical dealloying process for generating peculiar three‐dimensional (3D) free‐standing NPG with 'parting limit' as low as 25 % (lower than theoretical 'paring limit' 55 %) and high specific surface area (maximum ≈31 m 2 g −1 ) associated with a novel porous 'cone shaped protrusion' morphology. This NPG structure possesses the highest specific activity of MOR catalytic performance reported NPG catalysts so far. In addition, taking advantage of this excellent structural feature of the NPG, a nanoporous Pd catalyst (NPG@Pd) thin film was fabricated on the NPG substrate. The NPG@Pd catalyst exhibited greatly enhanced MOR performance (maximum MOR specific activity 2.14 mA cm −2 ). We attribute the enhancement of MOR activity to the increase of active sites as well as the modification of surface composition and electronic structure due to migration of Au to the Pd thin film layer. Abstract : 3D Nanoporous gold (NPG) was fabricated by facile chemical‐dealloying method, through which a novel porous ′cone shaped protrusion′ morphology was formed on the top of a surface. NPG@Pd catalyst was fabricated using this specific topology as a substrate to load Pd thin film and enhance methanol electro‐oxidation performance induced by metal migration effect between NPG substrate and Pd thin film.